Wildlife rescue - Costain, Meredith (Gosford, NSW : Scholastic Australia, 2020)
Ella's heart is breaking! She just can't stop thinking about the tiny BABY POSSUM that she found lost in the park. Where did the rescuer lady take the poor little thing? Will it be LONELY? What will it eat? Her friends Ammy and Zoe don't seem to care, but Ella is determined to find out!
Keywords: Girls -- Juvenile fiction; Phalangeridae -- Juvenile fiction; Australian